2009
DOI: 10.1016/j.bcp.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

STI571 sensitizes breast cancer cells to 5-fluorouracil, cisplatin and camptothecin in a cell type-specific manner

Abstract: Previously, we demonstrated that Abl kinases are highly active in invasive breast cancer cell lines, and contribute to survival in response to nutrient deprivation, invasion and proliferation. To determine whether an Abl kinase inhibitor, STI571 (Gleevec; imatinib mesylate) sensitizes breast cancer cells to chemotherapeutic agents, we treated three breast cancer cell lines (BT-549, MDA-MB-231, and MDA-MB-468) that have active Abl kinases, with STI571 in combination with several conventional chemotherapeutic dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…Some reports have shown that the inhibition of STAT3 could sensitize tumor cells to cisplatin-induced cell death [Sims et al, 2009;Liu et al, 2010;Yilmaz et al, 2010]. Therefore, we postulate that arctigenin may promote chemosensitivity of tumor cells to cisplatin through inhibition of STAT3 activity.…”
Section: Discussionmentioning
confidence: 78%
“…Some reports have shown that the inhibition of STAT3 could sensitize tumor cells to cisplatin-induced cell death [Sims et al, 2009;Liu et al, 2010;Yilmaz et al, 2010]. Therefore, we postulate that arctigenin may promote chemosensitivity of tumor cells to cisplatin through inhibition of STAT3 activity.…”
Section: Discussionmentioning
confidence: 78%
“…83 , and active c-Abl was localized in the cytoplasm, similar to BCRAbl and v-Abl. 84,85 Significantly, c-Abl/ Arg activities (assessed by phosphorylation of substrates, Crk/CrkL) were dramatically elevated in primary melanomas relative to benign nevi or normal skin. 83,79 We showed that constitutively active IGF-1R, Her-2, EGFR, and/or SFKs contributed to c-Abl/Arg activation in melanoma and breast cancer lines, ruling out mutation as the method of activation and uncovering a novel activation mechanism in solid tumors (Fig.…”
Section: Mechanisms Of C-abl and Arg Activation In Solid Tumorsmentioning
confidence: 99%
“…The reason for increased efficacy of imatinib in combination with cisplatin in chordoma is not clear yet. However, there is increasing preclinical evidence in favor of a synergic activity of these two agents in other cancers and, in particular, that imatinib can sensitize tumor cells to cisplatin [90][91][92][93], at least in some tumors. These data are somehow encouraging and surely deserve further investigation.…”
Section: Imatinib In Combination With Cisplatinmentioning
confidence: 99%